Vraaggerichte geestelijke zorg: Een antwoord op religieus pluralisme en secularisatie - Cadge, Wendy (Religie & Samenleving, 2020)
American society is increasingly characterized by secularization and religious pluralism. Therefore, citizens no longer turn to the predecessors of the traditional churches. Spiritual caregivers can respond to this development by working in a more demand-oriented way. Three pilot studies show how spiritual caregivers can respond to the new challenges. These cannot be addressed purely on an individual level, but also require an institutional approach.